2018
DOI: 10.1136/bcr-2017-222797
|View full text |Cite
|
Sign up to set email alerts
|

Skin and coeliac disease, a lot to think about: a case series

Abstract: Coeliac disease (CD) is an autoimmune disease, characterised by a permanent sensitivity to gluten. It is being progressively recognised as a multisystemic disease, with multiple extraintestinal manifestations. Skin conditions (eg, dermatitis herpetiformis) are an example of its manifestations; however, its underlying mechanisms are still not well understood. This article presents three cases of uncommon skin conditions in patients with a history of CD. Two of them concern linear IgA bullous dermatosis and eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Other hypothesized associations between skin disease and CD ( 7 , 8 , 23 ) include lupus erythematosus ( 68 ), dermatomyositis ( 69 ), Behçet disease ( 70 ), pemphigus ( 71 , 72 ), linear IgA bullous dermatosis ( 73 ), and lichen ( 74 , 75 ). Rarely, prurigo nodularis ( 76 ), cutaneous vasculitis ( 7 , 21 ), necrolytic migratory erythema ( 77 ), erythema nodosum ( 78 ), pityriasis lichenoides ( 79 ), porphyria ( 80 ), cutaneous amyloidosis ( 81 ), pityriasis rubra pilaris ( 82 ), erythroderma ( 83 ), partial lipodystrophy ( 84 ),generalized acquired cutis laxa ( 85 ), ichthyosis ( 86 ), atypical mole syndrome and congenital giant nevus ( 87 ) have also been described.…”
Section: Coeliac Diseasementioning
confidence: 99%
“…Other hypothesized associations between skin disease and CD ( 7 , 8 , 23 ) include lupus erythematosus ( 68 ), dermatomyositis ( 69 ), Behçet disease ( 70 ), pemphigus ( 71 , 72 ), linear IgA bullous dermatosis ( 73 ), and lichen ( 74 , 75 ). Rarely, prurigo nodularis ( 76 ), cutaneous vasculitis ( 7 , 21 ), necrolytic migratory erythema ( 77 ), erythema nodosum ( 78 ), pityriasis lichenoides ( 79 ), porphyria ( 80 ), cutaneous amyloidosis ( 81 ), pityriasis rubra pilaris ( 82 ), erythroderma ( 83 ), partial lipodystrophy ( 84 ),generalized acquired cutis laxa ( 85 ), ichthyosis ( 86 ), atypical mole syndrome and congenital giant nevus ( 87 ) have also been described.…”
Section: Coeliac Diseasementioning
confidence: 99%
“…Other reported and less frequent associations include lichen planus and lichen sclerosus [ 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ], linear IgA bullous dermatosis [ 139 , 140 ], prurigo nodularis [ 141 ], pityriasis rubra pilaris and erythroderma [ 142 ], erythema elevatum diutinum [ 143 , 144 , 145 ], necrolytic migratory erythema [ 146 , 147 , 148 ], pityriasis lichenoides [ 140 ], erythema nodosum [ 140 , 149 , 150 , 151 ], porphyria [ 152 , 153 ], cutaneous amyloidosis [ 154 ], generalized acquired cutis laxa [ 155 , 156 ], acquired hypertrichosis lanuginosa [ 157 ], ichthyosis [ 158 ], partial lipodystrophy [ 159 ], transverse leukonychia [ 160 ], atypical mole syndrome, and congenital giant nevus [ 161 ]. Finally, we want to mention that earlier studies reported an increased risk of malignant melanoma in patients with CD, but a recent study refuted this relation [ 162 ].…”
Section: Other Skin Conditions Found In Patients With CDmentioning
confidence: 99%
“…Other reported and less frequent associations include: lichen planus and lichen sclerosus [136][137][138][139][140][141][142][143][144], linear IgA bullous dermatosis [145,146], prurigo nodularis [147], pityriasis rubra pilaris and erythroderma [148], erythema elevatum diutinum [149][150][151], necrolytic migratory erythema [152][153][154], pityriasis lichenoides [146], erythema nodosum [146,[155][156][157], porphyria [158][159], cutaneous amyloidosis [160], generalized acquired cutis laxa [161][162][163], acquired hypertrichosis lanuginose [164], ichthyosis [165], partial lipodystrophy [166], transverse leukonychia [167], atypical mole syndrome, and congenital giant nevus [168]. Finally, we want to mention that earlier studies reported an increased risk of malignant melanoma in patients with CD, but a recent study has refuted this relation [169].…”
Section: Rosaceamentioning
confidence: 99%